Strain Transfer and Test Research of Stick-up Fiber Bragg Grating Sensors - Wang Bing; Wang Xiaoli (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Because of the flaws of fiber Bragg grating, needs to set up protective layer between the structure and fiber layer to protect the fiber grating. Firstly the strain transferring rules of the FBG sensors is analyzed, carefully analyze the main factors influencing the fiber Bragg grating strain sensor transfer, and analyze concretely effect of each factor, the fiber Bragg grating sensors embedded angle deviation is analyzed and influence on the measured results. Finally, by a series of repeated, coherent, dynamic and fatigue characteristic test, it is proved that the FBG sensor has applied value